Leveraging the universe : 7 steps to engaging life's magic - Dooley, Mike, 1961- (Atria Books ; Beyond Words, 2011)
A step-by-step guide to self-fulfillment explains how to tap the unlimited energy of the universe to transform a life in spite of personal circumstances, make appropriate choices, and align beliefs in accordance with goals.